Antimicrobial Analysis of Biosynthesized Lectin-Conjugated Gold Nanoparticles. (31st March 2022) - Alnashiri, Hassien M.; Aldakheel, Fahad M.; Binshaya, Abdulkarim S.; Alharthi, Nahed S.; Ahmed, Musthaq
Abstract : To enhance the bioactivity of molecules through nanoparticles is being tested which has potential use in sustained-release drug delivery systems and to enhance the therapeutic effectiveness of drugs. Our current investigation s is to conjugate lectin to that of a gold nanoparticle (GNP) surface without disturbing the bioactive properties and enhances the antibacterial activity of lectin. Au-lectin nanoparticles were checked for their hemagglutination activity, characterized by transmission electron microscopy (TEM) and UV-visible spectrophotometer. The antibacterial effect of nanoparticle lectin, Au salt nanoparticle, and conjugated Au-lectin was estimated by Kirby-Bauer disc method; MICs were determined by microbroth dilution and compared with ciprofloxacin. These tests were done using known species of bacterial strain of multidrug resistant. The hemagglutination activity of lectin was improved to fourfold after purification. Lectin and Au nanoparticles combined had a significant effect on the inhibition of bacterial growth. No significant differences were observed in the inhibition zone diameters from killed bacteria and its supernatant towards any of the tested organisms. Lectin-conjugated gold particles showed good efficacy as antimicrobial agents and the nanoparticle-killed bacteria to work against the viable population of the same bacterium and/or other bacterial species too.